Influence of rootstocks and pruning times on yield and on nutrient content and extraction in 'Niagara Rosada' grapevine - Tecchio, Marco Antonio [UNESP]; Moura, Mara Fernandes; Teixeira, Luiz Antonio Junqueira; Pires, Erasmo José Paioli [UNESP]; Leonel, Sarita [UNESP] (Embrapa Informação TecnológicaPesquisa Agropecuária Brasileira, 2014)
The objective of this work was to evaluate the influence of rootstocks and pruning times on yield and on nutrient content and extraction by pruned branches and harvested bunches of 'Niagara Rosada' grapevine in subtropical climate. The rootstocks 'IAC 766', 'IAC 572', 'IAC 313', 'IAC 571-6', and '106-8 Mgt' were evaluated. Treatments consisted of a combination between five rootstocks and three pruning times. At pruning, fresh and dry matter mass of branches were evaluated to estimate biomass accumulation. At harvest, yield was estimated by weighing of bunches per plant. Branches and bunches were sampled at pruning and at harvest, respectively, for nutrient content analysis. Nutrient content and dry matter mass of branches and bunches were used to estimate total nutrient extraction. 'Niagara Rosada' grapevine grafted onto the 'IAC 572' rootstock had the highest yield and dry matter mass of bunches, which were significantly different from the ones observed in 'Niagara Rosada'/'IAC 313'. 'Niagara Rosada' grafted onto the 'IAC 572' rootstock extracted the largest quantity of K, P, Mg, S, Cu, and Fe, differing from 'IAC 313' and 'IAC 766' in K and P extraction, and from '106-8 Mgt' in Mg and S extraction. Winter pruning results in higher yield, dry matter accumulation by branches, and total nutrient content and extraction.

O objetivo deste trabalho foi avaliar a influência de porta-enxertos e épocas de poda na produtividade e no teor e na extração de nutrientes por ramos removidos pela poda e pelos cachos na colheita da videira 'Niagara Rosada', em clima subtropical. Foram avaliados os porta-enxertos 'IAC 766', 'IAC 572', 'IAC 313', 'IAC 571-6' e '106-8 Mgt'. Os tratamentos consistiram de combinação de cinco porta-enxertos e três épocas de poda. Na ocasião da poda, avaliaram-se a massa de matéria fresca e seca dos ramos para estimar o acúmulo de biomassa. Na colheita, estimou-se a produtividade pela pesagem dos cachos por planta. Amostraram-se ramos e cachos na ocasião da poda e no momento da colheita, respectivamente, para análise dos teores de nutrientes. O teor de nutrientes e a massa de matéria seca dos ramos e dos cachos foram utilizados para estimar a extração total de nutrientes. A videira 'Niagara Rosada' enxertada no porta-enxerto 'IAC 572' apresentou maior produtividade e massa de matéria seca dos cachos, as quais diferiram significativamente das observadas em 'Niagara Rosada'/'IAC 313'. 'Niagara Rosada' enxertada sobre o porta-enxerto 'IAC 572' extraiu maior quantidade de K, P, Mg, S, Cu e Fe, tendo diferido de 'IAC 313' e 'IAC 766' na extração de K e P, e de '106-8 Mgt' na extração de Mg e S. As podas de inverno resultam em maior produtividade, acúmulo de matéria seca nos ramos, teor e extração total de nutrientes.
Influência de porta-enxertos e épocas de poda na produtividade e no teor e na extração de nutrientes na videira 'Niagara Rosada'
Keywords: Vitis labrusca; Vitis vinifera; acúmulo de biomassa; nutrição mineral; produtividade; Vitis labrusca; Vitis vinifera; biomass accumulation; mineral nutrition; yield